2020
DOI: 10.3390/jcm9061993
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in CCL18 Gene Influences CCL18 Expression and Correlates with Survival in Idiopathic Pulmonary Fibrosis—Part B

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive disease with high mortality. CC-chemokine ligand 18 (CCL18) is predictive of survival in IPF. We described correlation of CCL18 serum levels with the genotype of rs2015086 C > T polymorphism the CCL18-gene, which was associated with survival in a pre-antifibrotic cohort (Part-A). Herein (Part-B), we aimed to validate these findings and to study the effects of antifibrotics. Two cohorts were prospectively recruited, cohort-A (n = 61, pre-antifibrotic) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…In the anti-fibrosis treatment cohort, increased CCL18 was associated with poor prognosis. The genotype of the CCL18 gene promoter SNP has no predictive value; furthermore, CCL18 level increased no matter the effect of anti-fibrosis (nintedanib and pirfenidone) treatment [ 42 , 15 ]. Another study showed that CCL18 cannot predict the progression of IPF [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the anti-fibrosis treatment cohort, increased CCL18 was associated with poor prognosis. The genotype of the CCL18 gene promoter SNP has no predictive value; furthermore, CCL18 level increased no matter the effect of anti-fibrosis (nintedanib and pirfenidone) treatment [ 42 , 15 ]. Another study showed that CCL18 cannot predict the progression of IPF [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“… Majewski S, 2022 [ 14 ] YKL-40 Single-center, case-control study IPF: n = 25 Control subject: n = 20 24 Serum YKL-40 concentration may be related to the response to anti-fibrosis therapy of IPF patients. Caliskan C, 2020 [ 15 ] CCL18 Multicenter, prospective, cohort study Cohort A: n = 61 Cohort B: n = 126 Cohort A: 48 Cohort B: 36 Serum CCL18 level is associated with the CCL18 rs2015086 genotype and predicts mortality and disease progression of IPF patients. Akiyama N, 2020 [ 16 ] S100A4 Single-center, case-control study IPF: n = 95 Control subject: n = 50 24 High serum S100A4 level is independently associated with high disease progression and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that alveolar macrophages from patients with several types of fibrotic lung disease show increased expression of the pro-Th2-inflammatory cytokine CCL 18, which seems to represent a feed-forward mechanism in the fibrotic process [ 53 ]. CCL18 expression has been associated with survival in patients with IPF and patients with CTD-ILD due to systemic sclerosis [ 54 , 55 , 56 ]. Gene expression studies performed on peripheral blood also support the role of inflammatory processes in progression of IPF [ 57 , 58 , 59 , 60 ], and in IPF lungs there is increased expression of genes related to inflammatory processes in fibrotic and non-fibrotic areas [ 61 ].…”
Section: Application Of the ‘Treatable Traits’ Concept In Fibrotic Ildmentioning
confidence: 99%